Hydrothermal synthesis and electrochemical properties of V2O5 nanomaterials with different dimensions. Issue 10 (December 2015) - Mu, Juyi; Wang, Jinxing; Hao, Jinghua; Cao, Pin; Zhao, Shuoqing; Zeng, Wen; Miao, Bin; Xu, Sibo
Abstract: In the work, four types of typical morphologies of differently dimensional pure V2 O5 nanostructures including nanoflowers, nanoballs, nanowires and nanorods were synthesized through a simple hydrothermal method. The morphology of the product depends on the types of solvent and acid. Hierarchical nanoflowers and zero-dimensional (0D) nanoballs of V2 O5 nanocrystals were obtained when using C2 H5 OH as solvent. One dimensional (1D) nanowires and nanorods were obtained if H2 O was used to participate in the reaction. The morphology and structure of the samples were characterized by XRD and SEM, respectively. The electrochemical behaviors of nanoflowers, nanoballs, nanowires and nanorods as electrodes in a supercapacitor device were tested using cyclic voltammetry (CV) curves and galvanostatic charge–discharge (GCD) curves. The electrochemical test results indicate that the rod-like structure leads to a significant improvement of storage capacity, electrochemical kinetics and rate capability. And 1D V2 O5 nanorods show the largest specific capacitance of 235 F g −1 at the current density of 1 A g −1 when used as supercapacitor electrode in 1 mol/L Na2 SO4 electrolyte. It turns out that 1D V2 O5 nanorod is an ideal material compared with other morphologies for supercapacitor electrode.